Towards a conceptual framework for understanding and developing mathematical competence: A multi-dual perspective. Issue 1 (2nd January 2021) - Yang, Kai-Lin; Tso, Tai-Yih; Chen, Ching-Shu; Lin, Yuan-Horng; Liu, Shiang-Tung; Lin, Su-Wei; Lei, Kin Hang
ABSTRACT: Possessing the mathematical competence to encounter the challenges under globalisation and the ubiquity of digital technology is an important goal of education. Herein, we propose a broad conceptual framework for understanding and developing mathematical competence. The framework comprises four non-overlapping but interlinked cores: learning, knowing, applying, and viewing . Our framework encompasses ontological, epistemological, and pedagogical dimensions based on a multi-dual perspective. The proposed framework serves as a foundation for generating different learning paths to develop mathematical competence. Examples of learning paths are provided to illustrate the correlative and complementary relationships among the cores of mathematical competence.